The crime drop and the changing face of commercial victimization: Reflections on the 'commercial crime drop' in the UK and the implications for future research. (September 2016) - Hopkins, Matt
A growing body of research has both described and forwarded hypotheses to account for the crime drop that has been observed in many western countries since 1995. Commentators have focused on falls observed for households and individuals, with little reflection on the commercial sector. This is surprising given that previous research has recognized both the high rate of crime against some business sectors and the potential impact of crime against more economically vulnerable enterprises. This article explores the crime drop in relation to businesses in England and Wales. It considers whether there is evidence of a crime drop, the extent to which this appears to mirror the patterns observed for households/individuals and presents some tentative hypotheses to explain the patterns observed. Some suggestions are also made for areas that require further research.